Membrane electrode catalyst layer slurry, preparation method thereof and application of membrane electrode catalyst layer slurry in preparation of proton exchange membrane fuel cell

By adding alkali metal ions with a larger ion radius to the membrane electrode catalyst slurry, the perfluorosulfonic acid resin is prevented from self-aggregation, the problems of poor catalyst dispersion and uneven water distribution are solved, and the performance and stability of the membrane electrode are improved.

CN119252938APending Publication Date: 2025-01-03SINOHYKEY TECHNOLOGY FOSHAN CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411560093.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In proton exchange membrane fuel cell, self-aggregation of perfluorosulfonic acid resin in the catalyst slurry leads to poor dispersion of catalysts, degradation of catalytic layer performance, and prone to uneven water distribution.

Method used

By adding alkali metal ions with larger ion radius to the perfluorosulfonic acid resin film solution, the hydrogen bond between the resin is destroyed, the resin is prevented from self-aggregation, and more catalyst-resin interfaces are formed to improve the dispersion of the catalyst. and uniformity of the slurry.

Benefits of technology

Effectively reduce the particle size of the catalyst slurry, improve the surface morphology of the catalytic layer and the membrane electrode performance, reduce the roughness of the catalytic layer, improve the proton conduction ability, and avoid the problem of uneven water distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252938A_ABST
    Figure CN119252938A_ABST
Patent Text Reader

Abstract

The invention discloses membrane electrode catalyst layer slurry, a preparation method thereof and application of the membrane electrode catalyst layer slurry in preparation of a proton exchange membrane fuel cell, and relates to a membrane electrode material. The catalyst layer slurry comprises a resin dispersion liquid and a catalyst pre-dispersion suspension liquid; the resin dispersion liquid comprises alkali metal ions and a perfluorinated sulfonic acid resin film solution, the molar ratio of-SO3H in the alkali metal ions and perfluorinated sulfonic acid resin powder is larger than or equal to 0.05 and smaller than 0.3, and the alkali metal ions are Cs < + > and / or Rb < + >. A small amount of alkali metal ions with large ion radius are added into the catalyst layer slurry, so that self-agglomeration among perfluorosulfonic acid resin molecules is effectively blocked, more catalyst-perfluorosulfonic acid resin interfaces are generated, the particle size of the catalyst slurry is effectively reduced, the content of free perfluorosulfonic acid resin is reduced, and the service life of the catalyst slurry is prolonged. The uniformity of the catalyst slurry is remarkably improved, and on a catalyst layer of the CCM, the roughness is reduced, large particles on the surface are reduced, and the performance of a membrane electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of membrane electrode materials, and in particular to a membrane electrode catalyst layer slurry and a preparation method thereof and application thereof in the preparation of a proton exchange membrane fuel cell. Background Art

[0002] Membrane electrode is a key component of proton exchange membrane fuel cell, which is made of catalyst layer, proton exchange membrane, carbon paper, etc. Catalyst coated membrane (CCM) is its core part. CCM has a three-layer structure, with proton exchange membrane in the middle and catalyst layer on both sides. The catalyst layer is the place where the fuel cell reaction occurs, which is composed of catalyst and proton conductive perfluorosulfonic acid resin. The structure, three-phase interface, pores, hydrophilicity and hydrophobicity of the catalyst layer have a significant impact on the performance of the fuel cell, and the characteristics of the catalyst layer depend on the dispersion state of the catalyst slurry used for coating.

[0003] The perfluorosulfonic acid resin molecule consists of a hydrophobic polytetrafluoroethylene main chain and a hydrophilic sulfonated vinyl side chain. In addition to its function of conducting protons in the membrane electrode, it also acts as a dispersant in the catalyst slurry. In the catalyst slurry, the perfluorosulfonic acid resin interacts with the catalyst. Usually, the hydrophilic side chains of the perfluorosulfonic acid resin tend to be adsorbed on the platinum nanoparticles or platinum alloy nanoparticles of the catalyst, and the hydrophobic main chain of the perfluorosulfonic acid resin tends to be adsorbed on the carbon carrier of the catalyst.

[0004] Theoretically, the dispersed catalyst-perfluorosulfonic acid resin particles prevent reaggregation between particles through electrostatic repulsion, thus obtaining a well-dispersed catalyst slurry. In fact, in real catalyst slurries, especially high-solid content catalyst slurries suitable for slot coating, the concentration of perfluorosulfonic acid resin itself is high, and the primary aggregates of perfluorosulfonic acid resin molecules-SO 3 - will react with the protonated water molecule H 3 O + Form intermolecular hydrogen bonds and non-ionized -SO 3 The electrostatic attraction interaction between H causes the primary aggregates to aggregate to form larger secondary aggregates, which are difficult to effectively disperse the catalyst. Moreover, these aggregates are not easy to open and cannot be used, resulting in poor dispersion of the catalyst slurry, which is manifested as large catalyst slurry particles and the presence of perfluorosulfonic acid resin aggregates in the slurry. Furthermore, large particles in the catalyst slurry will cause a reduction in the effective three-phase interface in the catalyst layer and an increase in the roughness of the catalyst layer. The former causes a decrease in the performance of the membrane electrode, and the latter causes the risk of the proton exchange membrane being punctured. The perfluorosulfonic acid resin aggregates in the slurry will exist in the catalyst layer after being coated into the catalyst layer. These aggregates themselves have strong hydrophilicity, which can easily cause uneven water distribution in the catalyst layer during membrane electrode operation, leading to problems such as local flooding.

[0005] Therefore, solving the self-agglomeration problem of perfluorosulfonic acid resin in the slurry, improving the uniformity of catalyst-perfluorosulfonic acid resin adsorption, and obtaining a catalyst slurry with good dispersion are the keys to improving the morphology of the catalyst layer and improving the quality of the membrane electrode. Summary of the invention

[0006] The present invention provides a membrane electrode catalyst layer slurry and a preparation method thereof and application in the preparation of a proton exchange membrane fuel cell, which effectively reduces the self-agglomeration of a perfluorosulfonic acid resin in the catalyst layer slurry, improves the perfluorosulfonic acid resin-catalyst interface, thereby promoting the dispersion and particle uniformity of the catalyst, and improving the surface morphology of the catalyst layer and the membrane electrode performance.

[0007] In order to solve the above technical problems, one of the purposes of the present invention is to provide a membrane electrode catalyst layer slurry, including a resin dispersion and a catalyst pre-dispersed suspension;

[0008] The resin dispersion comprises alkali metal ions and a perfluorosulfonic acid resin membrane solution, wherein the perfluorosulfonic acid resin membrane solution comprises 10wt%-25wt% perfluorosulfonic acid resin powder and the remainder is an aqueous solution containing a low boiling point solvent. 3 The molar ratio of H is greater than or equal to 0.05 and less than 0.3, and the alkali metal ion is Cs + and / or Rb + ;

[0009] The catalyst pre-dispersed suspension comprises a catalyst and a solvent, wherein the solvent comprises water and / or an organic solvent, and the content of the perfluorosulfonic acid resin powder is 20wt%-80wt% of the catalyst mass.

[0010] If the perfluorosulfonic acid resins in the catalyst layer slurry are all in the acid form, hydrogen bonds are easily formed between the perfluorosulfonic acid resins, resulting in agglomeration during coating. In this application, a small amount of alkali metal ions with relatively large ionic radius, such as Cs + , Rb + , which can replace the protons in the perfluorosulfonic acid resin, destroy the hydrogen bonding between the perfluorosulfonic acid resins, and make some of the side chain sulfonic acid groups of the perfluorosulfonic acid resins replaced by their own -SO 3 H is converted to -SO 3 Cs or - SO 3Rb, due to the large ionic radius of Cs or Rb, it effectively blocks other perfluorosulfonic acid resin molecules from self-aggregating with it, thereby playing a role in separating perfluorosulfonic acid resin agglomerates, enhancing the interaction between catalyst and perfluorosulfonic acid resin, generating more catalyst-perfluorosulfonic acid resin interfaces, effectively reducing the particle size of catalyst slurry, enhancing the stability of catalyst slurry, improving the morphology of CCM catalyst layer and improving membrane electrode performance; further, the content of free perfluorosulfonic acid resin in the catalyst slurry is reduced, and the uniformity of the catalyst slurry is significantly improved, which is manifested in the catalyst layer of CCM as reduced roughness of the catalyst layer, reduced large particles on the surface, improved uniformity of the catalyst layer, and improved membrane electrode performance.

[0011] As a preferred embodiment, the Cs in the resin dispersion + It is provided by cesium salt and / or cesium hydroxide, wherein the cesium salt includes at least one of cesium fluoride, cesium sulfate, cesium carbonate, cesium nitrate, cesium chloride, cesium iodide, cesium bromide, cesium formate, cesium chromate, cesium bicarbonate, cesium perchlorate, cesium dichromate and cesium acetate.

[0012] As a preferred embodiment, Rb in the resin dispersion + It is provided by rubidium salt and / or rubidium hydroxide, wherein the rubidium salt includes at least one of rubidium fluoride, rubidium sulfate, rubidium carbonate, rubidium nitrate, rubidium chloride, rubidium iodide, rubidium bromide, rubidium formate, rubidium chromate, rubidium bicarbonate, rubidium perchlorate, rubidium chromate, and rubidium acetate.

[0013] As a preferred embodiment, the perfluorosulfonic acid resin membrane solution includes 10 wt%-25 wt% perfluorosulfonic acid resin powder, 20 wt%-40 wt% low boiling point solvent and the balance water.

[0014] As a preferred embodiment, the catalyst pre-dispersed suspension comprises 2wt%-16wt% catalyst, 10wt%-20wt% organic solvent and the balance water.

[0015] As a preferred embodiment, the low boiling point solvent includes at least one of methanol, ethanol, n-propanol, isopropanol and butanol, and the organic solvent includes at least one of methanol, ethanol, n-propanol, isopropanol and butanol.

[0016] As a preferred embodiment, the catalyst is a Pt / C catalyst and / or a PtM / C catalyst, M in the PtM / C catalyst is at least one of Co, Ni, Fe, Cu, Pd, Au, Ir, and Rh, and the Pt content in the catalyst is 30wt%-60wt%.

[0017] As a preferred embodiment, the Cs + and perfluorosulfonic acid resin powder -SO 3 The molar ratio of H is 0.05-0.15.

[0018] The present application controls the amount of alkali metal ions added. Although the introduction of alkali metal ions may cause a small amount of perfluorosulfonic acid resin to lose its ability to conduct protons, the reduction of the agglomeration of perfluorosulfonic acid resin will make the perfluorosulfonic acid resin that was originally unable to function inside the agglomerate be utilized, thereby improving the overall proton conduction capacity. However, when the alkali metal ions are added in excess, the reduction in the particle size of the catalyst layer slurry is not obvious enough, and the alkali metal ions will combine with a large amount of -SO 3 H, causing a large amount of perfluorosulfonic acid resin to lose the ability to conduct protons. Too much will reduce the proton conductivity of the catalyst layer, prolong the activation time of the membrane electrode, and reduce the performance of the membrane electrode. Therefore, the present invention contains alkali metal ions and -SO in the resin dispersion. 3 The optimal molar ratio of H is (0.05-0.15):1, which can effectively reduce the particle size of the catalyst layer slurry and reduce the self-agglomeration of the perfluorosulfonic acid resin, while improving the membrane electrode performance.

[0019] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing a membrane electrode catalyst layer, comprising the following steps:

[0020] (1) adding an alkali metal ion compound to a perfluorosulfonic acid resin film solution and stirring for 30-90 minutes to obtain a resin dispersion;

[0021] (2) mixing the catalyst with stirred water, ultrasonically treating in an ice bath at 1000-1200W for 5-10 min, then adding an organic solvent, and ultrasonically treating in an ice bath for 20-40 min to obtain a catalyst pre-dispersed suspension;

[0022] (3) adding the resin dispersion to the catalyst pre-dispersed suspension in a stirring state, stirring evenly, and ball milling for 1-3 hours to obtain a catalyst layer slurry;

[0023] (4) The catalyst layer slurry is coated on the side of the proton exchange membrane by a slit coating method, and dried at 60-100° C. to obtain a membrane electrode catalyst layer.

[0024] In order to solve the above technical problems, the third object of the present invention is to provide a membrane electrode catalyst layer.

[0025] In order to solve the above technical problems, a fourth object of the present invention provides an application of a membrane electrode catalyst layer in the preparation of a proton exchange membrane fuel cell.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. This application adds a small amount of alkali metal ions with relatively large ionic radius, such as Cs + , Rb +, effectively blocking the self-agglomeration of perfluorosulfonic acid resin molecules, enhancing the interaction between catalyst and perfluorosulfonic acid resin, producing more catalyst-perfluorosulfonic acid resin interfaces, effectively reducing the particle size of catalyst slurry, reducing the content of free perfluorosulfonic acid resin in the catalyst slurry, and significantly improving the uniformity of the catalyst slurry. On the catalytic layer of CCM, it is manifested as reduced roughness of the catalytic layer, reduced large particles on the surface, improved uniformity of the catalytic layer, and improved membrane electrode performance.

[0028] 2. The present application controls the amount of alkali metal ions added, reduces the agglomerates of perfluorosulfonic acid resin, and can effectively reduce the particle size of the catalyst layer slurry, so that the perfluorosulfonic acid resin that was originally unable to function inside the agglomerates can be utilized, thereby improving the overall proton conductivity and membrane electrode performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 : It is a statistical chart of the particle size results of the catalyst layer slurry in the embodiments of the present invention and the comparative examples;

[0030] Figure 2 : It is a statistical chart of the particle size of the protruding particles on the surface of the catalyst layer in the embodiments of the present invention and the comparative examples;

[0031] Figure 3 : is a relative viscosity curve of the resin dispersion in the embodiment of the present invention and the comparative example as the shear rate changes;

[0032] Figure 4 : is a polarization curve chart of the membrane electrode prepared by the catalyst layer in the embodiments of the present invention and the comparative examples;

[0033] Figure 5 : are the contact angle test results of the catalyst layer surface in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The following Table 1 shows the sources and types of raw materials used in the examples and comparative examples of the present application. Unless otherwise specified, the raw materials used can be obtained commercially, and the same raw materials are used in parallel experiments.

[0036] Table 1 - Sources of raw materials used in the examples and comparative examples of this application

[0037]

[0038] Example 1

[0039] A membrane electrode catalyst layer slurry, the preparation method of which comprises the following steps:

[0040] (1) Add cesium carbonate to 30 g of perfluorosulfonic acid resin membrane solution A. The cesium ion Cs in cesium carbonate + and sulfonate-SO in perfluorosulfonic acid resin membrane solution A 3 The molar ratio of H was 0.05:1, and the resin dispersion was obtained after stirring for 60 min;

[0041] (2) 5.1 g of a Pt / C catalyst having a Pt content of 50 wt% was weighed and slowly added to 39 g of ultrapure water in a stirring state, and ultrasonicated at 1000 W in an ice bath for 5 min. Then, 7.2 g of n-propanol was added thereto, and ultrasonicated at an ice bath for 30 min to obtain 51.6 g of a catalyst pre-dispersed suspension;

[0042] (3) adding 11.0 g of the resin dispersion to the entire catalyst pre-dispersed suspension in step (2) above in a stirring state, stirring for 2 min, and then ball milling for 2 h to obtain a catalyst layer slurry;

[0043] (4) The catalyst layer slurry is coated on the side of the proton exchange membrane by slit coating, and dried at 80° C. to obtain a membrane electrode catalyst layer.

[0044] Example 2

[0045] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), the cesium ion Cs of the cesium carbonate in the resin dispersion is + and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.1:1.

[0046] Example 3

[0047] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), the cesium ion Cs of the cesium carbonate in the resin dispersion is + and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.15:1.

[0048] Example 4

[0049] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), cesium carbonate is replaced by cesium hydroxide, and the cesium ion Cs of cesium hydroxide in the resin dispersion is + and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.05:1.

[0050] Example 5

[0051] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), cesium carbonate is replaced by cesium chloride, and the cesium ion Cs in the cesium chloride in the resin dispersion is + and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.05:1.

[0052] Example 6

[0053] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), rubidium carbonate is used instead of cesium carbonate, and the rubidium ion Rb of the rubidium carbonate in the resin dispersion is + and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.05:1.

[0054] Comparative Example 1

[0055] A membrane electrode catalyst layer slurry, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), the amount of cesium carbonate added is 0.

[0056] Comparative Example 2

[0057] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), the cesium ion Cs of the cesium carbonate in the resin dispersion is + and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.3:1.

[0058] Comparative Example 3

[0059] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), sodium carbonate is used instead of cesium carbonate, and the sodium ions Na of the sodium carbonate in the resin dispersion are+ and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.05:1.

[0060] Comparative Example 4

[0061] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), cerium nitrate is used instead of cesium carbonate, and the cerium ion Ce in the resin dispersion is 3+ and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.05:1.

[0062] Comparative Example 5

[0063] A membrane electrode catalyst layer slurry, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), perfluorosulfonic acid resin membrane solution A is replaced by perfluorosulfonic acid resin membrane solution B in equal amounts, and perfluorosulfonic acid resin membrane solution B comprises 28 wt% perfluorosulfonic acid resin powder, 30 wt% water and 42 wt% methanol.

[0064] Comparative Example 6

[0065] A membrane electrode catalyst layer slurry, wherein the steps of the preparation method and the reagents, equipment and process parameters used in the steps are the same as those in Example 1, except that in step (1), the cesium ion Cs of the cesium carbonate in the resin dispersion is + and sulfonate-SO of perfluorosulfonic acid resin membrane solution A 3 The H molar ratio is 0.02:1.

[0066] Performance Testing

[0067] 1. The particle size D of the catalyst slurry of the embodiment and the comparative example was measured by laser particle size analyzer. Avg , D 50 , D 90 , D 100 The particle size results are as follows Figure 1 And as shown in Table 2.

[0068] 2. The surface of the membrane electrode catalyst layer prepared in the examples and comparative examples was subjected to SEM test, and the particle sizes of 200 protruding particles on the surface of the catalyst layer were counted. The statistical results of Examples 1, 3 and Comparative Examples 1-2 are as follows: Figure 2 And as shown in Table 2.

[0069] 3. The shear viscosity change of the resin dispersion (ionomer dispersion) in step (1) of the embodiment and the comparative example was tested using a rheometer. The test conditions were 25°C, 0.001s -1~100s -1 , the test results are as follows Figure 3 As shown, the shear rate was recorded at 100 s -1 The relative viscosity is shown in Table 2.

[0070] 4. The membrane electrode catalyst layer prepared in the embodiment and the comparative example was used to prepare a membrane electrode, and the polarization performance curve of the membrane electrode single cell was tested using the 850e fuel cell test system. The test conditions were: battery temperature: 85°C, anode / cathode humidity: 60 / 40% RH, anode / cathode gas pressure: 130 / 90 kPa, and the test standard was referenced to GB / T 28817-2022. The test results are as follows: Figure 4 shown.

[0071] 5. Take the catalyst layer slurry of the embodiment or comparative example, use a 0.22 μm aqueous filter membrane to vacuum filter the slurry, collect the filtrate, dry it at 150°C until the mass remains unchanged, and weigh it to obtain the mass of free ionomer in the slurry. The test results are shown in Table 2 below.

[0072] 6. The contact angle of the catalyst layer surface of the embodiment or comparative example was measured with reference to GB / T 30693-2014 standard. Water droplets were dropped on the catalyst layer surface to measure the contact angle formed by the water droplets on the catalyst layer surface. The test results are shown in Tables 2 and Figure 5 shown.

[0073] Table 2 - Performance test results of membrane electrode catalyst layer and slurry of the present application examples and comparative examples

[0074]

[0075]

[0076] like Figure 1 As shown in Table 2, Examples 1-3 add Cs + The particle size of the catalyst layer slurry is smaller than that of the comparative example 1 without adding Cs + Catalytic layer slurry, a small amount of Cs + The addition reduces the agglomerates of perfluorosulfonic acid resin, increases the free ionomers, and increases the effective catalyst-ionomer interface, which is beneficial to increase the effective three-phase interface of the catalytic layer. The membrane electrode performance is simultaneously improved, the large particles ≥10μm on the surface of the catalytic layer are significantly reduced, and the contact angle is smaller, which means that the surface of the catalytic layer of Examples 1-3 has stronger water absorption, which is conducive to the wetting of the membrane electrode.

[0077] like Figure 3-4 As shown in Table 2, the schemes of Example 1, Comparative Example 1 and Comparative Example 3 are compared. The ionomer dispersion used in Example 1 contains Cs + , Comparative Example 1 did not add, and Comparative Example 3 added Na+ It can be found that when Cs is added to the ionomer dispersion + The relative viscosity of the ionomer dispersion will decrease significantly, while adding an equal amount of Na + Although the relative viscosity of the dispersion is also lower than that of Comparative Example 1, the degree of decrease is much less than that of Example 1 when an equal amount of Cs is added. + , indicating adding Cs + The effect of improving the dispersion of ionomers is better than that of adding Na + .

[0078] like Figure 1 As shown in Table 2, in Examples 1-3, Cs + and-SO 3 When the molar ratio of H is in the range of (0.05-0.15):1, the particle size of the catalyst slurry is significantly smaller than that of Cs in Comparative Example 2. + and-SO 3 The molar ratio of H is 0.3:1 and the Cs + and-SO 3 The slurry particle size with a molar ratio of 0.02:1 is still smaller than that of Comparative Example 1, but the Cs + The effect of adding too much or too little on the reduction of slurry particle size is not as obvious as in Examples 1-3. + It will cause the water absorption capacity of the resin to deteriorate, thus affecting the dispersion of the resin. Too little Cs + The agglomeration of the perfluorosulfonic acid resin cannot be effectively prevented, so that the slurry particles are still large in size.

[0079] like Figure 2 , 4 As shown in Table 2, although the particle sizes on the catalyst layer surface of Examples 1, 3 and Comparative Example 2 are smaller than those of Comparative Example 1, the addition of excessive Cs + When Cs + Combined with a large amount of -SO 3 H, causing a large amount of resin to lose the ability to conduct protons, resulting in a decrease in polarization performance, indicating that Cs + and-SO 3 The optimal molar ratio of H is (0.05-0.15):1.

[0080] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A membrane electrode catalyst layer slurry, characterized in that: It includes a resin dispersion and a catalyst pre-dispersed suspension; The resin dispersion comprises alkali metal ions and a perfluorosulfonic acid resin membrane solution, wherein the perfluorosulfonic acid resin membrane solution comprises 10wt%-25wt% perfluorosulfonic acid resin powder, and the remainder is an aqueous solution containing a low boiling point solvent, wherein the molar ratio of the alkali metal ions to -SO3H in the perfluorosulfonic acid resin powder is greater than or equal to 0.05 and less than 0.3, and the alkali metal ions are Cs + and / or Rb + ; The catalyst pre-dispersed suspension comprises a catalyst and a solvent, wherein the solvent comprises water and / or an organic solvent, and the content of the perfluorosulfonic acid resin powder is 20wt%-80wt% of the catalyst mass.

2. A membrane electrode catalyst layer slurry as claimed in claim 1, characterized in that: The Cs in the resin dispersion + The cesium salt is provided by cesium salt and / or cesium hydroxide, wherein the cesium salt includes at least one of cesium fluoride, cesium sulfate, cesium carbonate, cesium nitrate, cesium chloride, cesium iodide, cesium bromide, cesium formate, cesium chromate, cesium bicarbonate, cesium perchlorate, cesium dichromate and cesium acetate; Rb in the resin dispersion + It is provided by rubidium salt and / or rubidium hydroxide, wherein the rubidium salt includes at least one of rubidium fluoride, rubidium sulfate, rubidium carbonate, rubidium nitrate, rubidium chloride, rubidium iodide, rubidium bromide, rubidium formate, rubidium chromate, rubidium bicarbonate, rubidium perchlorate, rubidium chromate, and rubidium acetate.

3. The membrane electrode catalyst layer slurry according to claim 1, characterized in that: The perfluorosulfonic acid resin membrane solution comprises 10 wt % to 25 wt % of perfluorosulfonic acid resin powder, 20 wt % to 40 wt % of a low boiling point solvent and the balance of water.

4. The membrane electrode catalyst layer slurry according to claim 1, characterized in that: The catalyst pre-dispersed suspension comprises 2wt%-16wt% of catalyst, 10wt%-20wt% of organic solvent and the balance of water.

5. The membrane electrode catalyst layer slurry according to claim 1, characterized in that: The low boiling point solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, and butanol, and the organic solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, and butanol.

6. The membrane electrode catalyst layer slurry according to claim 1, characterized in that: The catalyst is a Pt / C catalyst and / or a PtM / C catalyst, wherein M in the PtM / C catalyst is at least one of Co, Ni, Fe, Cu, Pd, Au, Ir, and Rh, and the content of Pt in the catalyst is 30wt%-60wt%.

7. The membrane electrode catalyst layer slurry according to claim 1, characterized in that: The molar ratio of the alkali metal ions to -SO3H in the perfluorosulfonic acid resin powder is 0.05-0.

15.

8. A method for preparing a membrane electrode catalyst layer, characterized in that: Using a membrane electrode catalyst layer slurry as described in any one of claims 1 to 7, comprising the following steps: (1) adding an alkali metal ion compound to a perfluorosulfonic acid resin film solution and stirring for 30-90 minutes to obtain a resin dispersion; (2) mixing the catalyst and water in a stirring state, ultrasonically treating in an ice bath at 1000-1200W for 5-10 minutes, then adding an organic solvent, and ultrasonically treating in an ice bath for 20-40 minutes to obtain a catalyst pre-dispersed suspension; (3) adding the resin dispersion to the catalyst pre-dispersed suspension in a stirring state, stirring evenly, and ball milling for 1-3 hours to obtain a catalyst layer slurry; (4) The catalyst layer slurry is coated on the side of the proton exchange membrane by a slit coating method, and dried at 60-100° C. to obtain a membrane electrode catalyst layer.

9. A membrane electrode catalyst layer prepared by the method for preparing a membrane electrode catalyst layer according to claim 8.

10. Use of the membrane electrode catalyst layer as claimed in claim 9 in the preparation of a proton exchange membrane fuel cell.

Citation Information

Cited By

  • Laser solid-phase in-situ constructed integrated membrane electrode and preparation method thereof

    CN121161329A